Profil Respon Time Pelayanan Darah di PMI Kabupaten Kuningan - Zhaika Salsabila; Francisca Romana Sri Supadmi; Deby Zulkarnain Rahardian Syah (Poltekkes Kemenkes Semarang, 2022)
One tangible manifestation of the provision of public services in the health sector is the Blood Transfusion Unit (UTD) which provides blood services. Blood Transfusion Services are health service efforts that include planning, mobilizing and preserving blood donors, supplying blood, distributing blood, and providing medical treatment to patients for the purpose of healing illness and restoring health. The Indonesian Red Cross, hereinafter abbreviated as PMI, is a social organization whose main tasks and functions are in the field of kepalangmerahan based on statutory provisions. Efforts to meet the availability of blood for the needs of health services so far have been made by PMI through UTD spread throughout Indonesia based on assignments by the Government In chapter II article 2 paragraph 1 PMK Number 83 of 2014 concerning blood transfusion units, hospital blood banks, and service networks blood transfusion is stated that: UTD is only held by the Government, Regional Government, or PMI. This research is a type of descriptive quantitative research. The approach used is cross sectional. The average blood service time at PMI Kuningan Regency in 2020 is 1 hour and can be completed in a minimum time of 35 minutes and a maximum of 3 hours 57 minutes. The stages that contribute to the length of blood service time are in the post-analytic stage and factors that influence the service time in the Kuningan Regency PMI laboratory, namely, the number of officers, length of service and facilities.